2023
DOI: 10.3389/fped.2022.1027894
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum brain-derived neurotrophic factor and cognitive impairment in children with sleep-disordered breathing

Abstract: BackgroundAs an important neuroprotective factor, the brain-derived neurotrophic factor (BDNF) may have a key role in cognitive impairment in children with sleep-disordered breathing (SDB). The main aim of this study was to compare the levels of BDNF and tyrosine kinase receptor B (TrkB) in normal children and those with obstructive sleep apnea (OSA) and primary snoring (PS) and to explore a possible link between BDNF/TrkB, inflammation, and SDB with cognitive impairment in children.MethodsA total of 44 OSA ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Out of all articles included in the meta-analysis, eighty-five articles were reported that dealt with adults [8,16,21,[31][32][33] while seventeen considered children [12,13,34,35,[121][122][123][124][125][126][127][128][129][130][131][132][133]. The studies are from various countries, including Egypt, China, Iran, USA, Saudi Arabia, Greece, Spain, India, Turkey, Brazil, Italy, Poland, Hungary, and France.…”
Section: Characteristics Of Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of all articles included in the meta-analysis, eighty-five articles were reported that dealt with adults [8,16,21,[31][32][33] while seventeen considered children [12,13,34,35,[121][122][123][124][125][126][127][128][129][130][131][132][133]. The studies are from various countries, including Egypt, China, Iran, USA, Saudi Arabia, Greece, Spain, India, Turkey, Brazil, Italy, Poland, Hungary, and France.…”
Section: Characteristics Of Articlesmentioning
confidence: 99%
“…These meta-analyses were conducted on OSA [ 24 , 25 , 26 ], interleukin (IL-8 in adults [ 27 ], IL-8 and IL-1β in both children and adults [ 28 ], TNF-α and IL-8 in adults [ 29 ], IL-8 in both children and adults [ 30 ], and TNF-α in both children and adults [ 20 ] in comparison to control groups. The outcomes of these meta-analyses varied, as did the results reported in the original articles [ 31 , 32 , 33 , 34 , 35 ]. The conflicting results in these meta-analyses could be due to several factors such as differences in study populations (age, ethnicity, and health status), variations in the methodologies used in the studies (measurement techniques and statistical analyses), and the inherent biological variability in cytokine levels.…”
Section: Introductionmentioning
confidence: 99%